Lack of Correct Writing and Critical Attitude in Expressing Syntactic Principles Critique of Form and Content in the Book of Syntactic Theory in the Form of Argumentative Commentary on Mughni al-Adib - Malik Abdi (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
Criticism, as a surgical process of literary texts, seeks to express the weaknesses of scientific works and then to explain the strengths and highlight their positive aspects. As one of the meanings of critique in the Arabic word is to take the bird’s grain and beak it to remove the healthy grain and to remove the defective and rotten grain. The science of syntax as one of the important disciplines of linguistics has been a strategic weapon of explorers of literary texts, and has always been considered by thinkers to provide critique and to write about scientific compositions. The book under review is an attempt to document some of the syntactic titles presented in the book "Mughni al-Adib", which is itself a new version of "Mughni al-Labib" by Ibn Hisham Ansari. This research is based on a descriptive-analytical method, and the results indicate that there is almost no trace of modernity in reasoning, and the presentation had solid and convincing approach in work. The explanations given by the author under the title of "syntactic revolution" are generally either incorrect, or quoting one of the famous opinions of its predecessors without mentioning their opinion, or attributing some of these opinions to themselves as a new argument and It is the syntactic initiative of the author. The rhythm of the book is also slow, monotonous and boring, and it does not have an attractive shape in terms of writing and processing. Thora’s syntactic book is generally an undocumented, unsubstantiated quasi-scientific work that is far removed from the reference system and is in fact, an unstable and weakened version of important sources in the field.